Tweet, set, match: negotiating the boundaries of digital technologies in elite tennis - Subramanian, V.; Noel, M.; Paquin, H. (Science, Technology and Society, 2020)
This article attempts to examine the highest tier of elite tennis through a technological lens in order to understand the several imbrications of tennis and technology in Grand Slam events. Using qualitative and quantitative methods, this article studies the version of tennis that exists today—replete with RFID chips, screen interfaces, more powerful racquets than ever before and the ubiquity of social media. As the relationship between players and fans, organisers and visitors, and even gameplay and umpiring have evolved to allow the use of several technologies, Grand Slam tennis has embraced the era of social media and technologically mediated sport. This article views this transformation through the lens of Science Technology and Society in order to better understand the influence that technologies have in shaping the relationships between spectators, players, matches, tournaments and indeed the sport itself.